The main factor that influences the effect of job rotation in Maybank Islamic Bangsar / Noor Amirah Azmi - Azmi, Noor Amirah (2016)
Job rotation involves an employee changing positions within the same organization and eventually returning to the original position. It can refer to different types of rotations. Maybank Islamic had adopted a job rotation program to help solve skills acquisition and performance problems of their employees. The problem this thesis attempted to investigate was that in addition to economic objective that every employee requires from his employer, when employee are allowed to perform the same transactional duties over many years, they feel bored and unsatisfied by doing the same kind of work over time. This development may affect job satisfaction and ultimately productivity. To achieve the objectives of the research, an exploratory and descriptive design were adopted aimed at assessing the main factor that influence the effect of job rotation. Thus, this study aims to identify the main factor that influences the effects of job rotation in Maybank Islamic Bangsar. Survey methodology was used for this research. A total of 86 questionnaires were returned and used to measure the three independent variables which are personnel development, Islamic Banking knowledge and motivation that can gives effect towards job rotation. Based on the result, personnel development is the main factor that influence job rotation.